Kultura bezpieczeństwa w imprezach masowych w Wielkopolsce. Analiza działań Miejsko-Wojewódzkiego Sztabu Operacyjnego Euro 2012 w Poznaniu - Magiera, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The narrow sense of security, reduced to the ability to survive, has nowadays become insufficient in terms of what society demands. As a result of globalization processes (and the dynamization of reality), the will to maintain a high standard of living (consumerism) and the increasing awareness of individuals in Western culture, the need for a comprehensive minimization of risk has emerged, and hence a demand to look for potential threats in practically every field of life, in order to identify and eradicate them. By means of referring to the culture of security, or – to be more precise – to its three components (resources, organization and mentality), the social expectations of the public administration can be identified. This pa- per reflects the expectations of the citizens of Wielkopolska as regards the security of mass events on the basis of the operations of the Urban-Regional Headquarters of Euro 2012 in Poznań (and the standards and factors influencing its decision-making status).
Culture of security during mass events in Wielkopolska. An analysis of the operations of the urban-regional headquarters of Euro 2012 in Poznań
Keywords: bezpieczeństwo; kultura bezpieczeństwa; Euro 2012; imprezy masowe